Flavonoids as Potent Phytochemicals in Cardiovascular Diseases Prevention - Harnafi, Hicham; Amrani, Souliman (Pharmacognosy Reviews)
Flavanoids are the major plant phenolic secondary metabolites and represent the most studied phytochemicals. This family includes five major classes different by their specific chemical structure,we note: flavones, flavonols, flavanones, flavanols and anthocyanidins. Many epidemiological and experimental studies have shown that flavonoid intake is inversely correlated with cardiovascular disease events. In this field, a number of flavonoids from medicinal plants, fruits, vegetables, spices and beverages have been shown to beneficially affect parameters associated with cardiovascular diseases, including hyperlipemia and especially hypercholesterolemia, low density lipoprotein oxidation, blood platelet aggregation, and vascular reactivity. Therapeutic effects of flavonoids on lipid metabolism disorder have been attributed to effective diminution of total cholesterol, Triglycerides, LDL-Cholesterol and Apo B levels. On the other hand, their beneficial effect results also in an increase of HDLcholesterolol, bile acids secretion and lipid catabolism. Furthermore, flavonoids play a pivotal role in preventing CVD related to oxidative stress via four distinct mechanisms including direct free radicals scavenging, pro-oxidant metal ions chelating, lipid peroxidation attenuation by recycling other antioxidants and preservation of the HDL-associated paraoxonase activity which has been shown to prevent oxidation of LDL particles. Moreover, flavonoids are able to inhibit cellular enzymes, implicated in cellmediated oxidation of LDL particles including phospholipase A2, cyclooxygenase and lipoxygenase, GSH reductase, xanthine oxidase and NADPH-oxidase. Flavonoids also protect platelet aggregation and related vascular complications through an increase of cAMP levels leading to intracellular Ca++ lowering, an inhibition of thromboxane formation and thromboxane receptor antagonism. Plus, these phytochemicals are able to play an important role on the endothelial function in regard to preventing hypertension via eNOS stimulation. The promising findings on biological activities of plant flavonoids can guide studies of the biochemical mechanisms underlying the protective effect of these compounds at arterial and cardiac levels to uncover new strategies for the treatment of vascular diseases and cardiac related complications.
Keywords: Flavonoids; cardiovascular diseases; hypercholesterolemia; LDL oxidation; vasorelaxation; platelet aggregation